Fear of Missing Out and Impulse Buying in the Digital Economy: The Mediating Role of Emotional Arousal in a Cross-border Indonesia–Malaysia Setting - Syahran Syahran; Erick Karunia; Deni Marsha; Imelda Yoshica Izzaurajz; Rika Armila (Universitas Negeri Yogyakarta, 2026)
The digital economy and social commerce have transformed consumer spending patterns, particularly in border regions such as North Kalimantan, where consumers are increasingly exposed to cross-border marketplaces and digital promotional stimuli. Promotions emphasizing urgency, scarcity, and discounts may intensify consumers’ fear of missing out and stimulate emotional arousal, thereby encouraging impulse buying even among well-educated and financially stable consumers. This study examines the influence of fear of missing out on impulse buying behavior in the Indonesia–Malaysia border region, with emotional arousal positioned as a key psychological mechanism linking digital marketing stimuli to spontaneous purchasing decisions. Drawing on structural equation modeling, the findings reveal that fear of missing out has a significant positive effect on both emotional arousal and impulse buying, while emotional arousal further strengthens consumers’ tendency to engage in impulse buying. These findings contribute to the literature on digital consumer psychology by highlighting the role of emotional mechanisms in cross-border social commerce contexts. In practice, the study offers insights for businesses and policymakers on designing digital marketing strategies that are persuasive yet ethical, while also supporting consumer protection in border regions